America’s Brain Drain: International Scientists and the Shifting Global Landscape - Majumdar, Sonali (International Higher Education, 2025)
Despite their central role in US research and innovation, international doctoral students now face significant instability, as restrictive immigration policies, declining research funding, and an unwelcoming climate push international scientists to seek careers abroad. Competing nations are seizing the moment through targeted recruitment of scientific talent and funding incentives. Without reform, the United States risks ceding its long-held edge in science and technology to global competitors.